Structural, Mechanical and Optical Properties of Plasma-chemical Si-C-N Films - A.O. Kozak; V.I. Ivashchenko; O.K. Porada; L.A. Ivashchenko; T.V. Tomila (Журнал нано- та електронної фізики)
An influence of the substrate temperature in the range of 40-400 °C on the properties of the Si-C-N films deposited by plasma enhanced chemical vapor deposition (PECVD) technique using hexamethyldisilazane is analyzed. Study of the structure, chemical bonding, surface morphology, mechanical properties and energy gap of the obtained films was carried out using X-ray diffraction, infrared spectroscopy, X-ray photoelectron spectroscopy, atomic force microscopy, optical measurements and nanoindentation. It was established that all the films were X-ray amorphous and had low surface roughness. Intensive hydrogen effusion from the films takes place, when substrate temperature increases up to 400 °C, which promotes a decrease of roughness and an increase in hardness and Young modules more than twice.